2019
DOI: 10.1021/acsnano.9b05740
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanostructuring of Porous Silicon with Electrochemical and Regenerative Electroless Etching

Abstract: Hierarchically nanostructured silicon was produced by regenerative electroless etching (ReEtching) of Si powder made from pulverized anodized porous silicon. This material is characterized by ∼15 nm mesopores, into the walls of which tortuous 2–4 nm pores have been introduced. The walls are sufficiently narrow that they support quantum-confined crystallites that are photoluminescent. With suitable parameters, the ReEtching process also provides control over the emission color of the photoluminescence. Ball mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…As expected, hydrosilylation changed the PL response and extended the useful range of pH values into the range encountered in PBS. As reported previously [42], exposure to phosphate buffer first enhanced PL intensity. Here, we found that the intensity variation depended on the pH of the Rinsing must achieve three imperatives to be effective for retaining maximum PL intensity.…”
Section: Ph Dependencesupporting
confidence: 84%
See 2 more Smart Citations
“…As expected, hydrosilylation changed the PL response and extended the useful range of pH values into the range encountered in PBS. As reported previously [42], exposure to phosphate buffer first enhanced PL intensity. Here, we found that the intensity variation depended on the pH of the Rinsing must achieve three imperatives to be effective for retaining maximum PL intensity.…”
Section: Ph Dependencesupporting
confidence: 84%
“…For comparison of H-terminated to hydrosilylated por-Si, ReEtched por-Si batches were functionalized by thermal hydrosilylation by immersing particles in undecylenic acid (99%, Agros Organics, Fisher Scientific, Pittsburgh, PA, USA) and heating them at 120 • C for 16 h as described in [42]. After heating, excess acid was removed by washing the resulting particles with ethanol (EtOH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodegradable scaffolds for tissue regeneration are clearly a good example of this, where the ability to control topography from nanometers to millimeters is required. The hierarchical structuring of silicon is being developed for numerous application areas shown in Table 4 [81][82][83]. In this regard, using a hierarchical biogenic silica template (Section 2.3) rather than multiple processing tools is particularly attractive, provided its dimensionality and topography are already optimized by nature for the specific use in mind.…”
Section: Biodegradable Silicon and Biomaterials Sciencementioning
confidence: 99%
“…[168] The performance of photoluminescence sensors may be tuned by optimizing nano dots and pore dimensions in porous silicon. Furthermore, chemical passivation of the oxide-free substrates is known to stabilize the photoluminescence [75,169] and prevent recombination. Therefore, organic interlayer prepared via hydrosilylation or electrografting that both conserve the photoluminescent properties as well as allow further biofunctionalization may play a great role in these devices.…”
Section: Sensor Typementioning
confidence: 99%